Analisis Kandungan Proksimat Daging Buah dan Biji Tiga Varietas Durian (Durio zibethinus Murr.) yang Berasal dari Tempat Tumbuh yang Berdekatan - Rusmiati Rusmiati; Sasi Gendro Sari; Karlina Rizki Amalia (Bioscientiae, 2021)
Studies to compare the proximate content of durian fruit flesh and seeds have not been widely employing. Hence, this study aimed to analyze and compare this content in fruit flesh and seeds of three durian varieties from adjacent growing areas. The following methods used for proximate analysis were carbohydrates (by difference), protein (micro Kjeldahl), lipid (soxhlet), crude fiber (washing), moisture content (oven), ash content (furnace). In evaluating the difference in proximate content in these parts of three durian varieties, the resulting data were tested statistically using ANOVA =5%, followed by the DMRT test. In determining the difference in the proximate content between the fruit flesh and durian seeds, the independent samples T-test was used with =5%. All data collected were then compared with the USDA National Nutrient and the Directorate of Nutrition at the Ministry of Health databases. The results showed that three durian varieties from adjacent growing areas had significantly different protein and carbohydrate content (in fruit flesh), ash content, protein, and carbohydrates (in seeds). The flesh part of the three varieties of durian contains water, protein, fat, crude fiber, which is significantly different from durian seeds. This study is higher than the comparison data